Factors affecting the commercialization of cellular based therapeutics - Pettitt, D (2018)
Introduction Cell based therapeutics represent a commercially and clinically important treatment modality that offers a transformative approach to managing untreatable diseases. However, despite promising global demand and mounting investor appetite, the translation of cellular based therapeutics from “bench-to-bedside” remains challenging. This research systematically delineates the commercialization pathway and offers viable solutions to expedite clinical translation. Methods A systematic review was conducted to establish principal factors in the commercialization pathway. Two independent reviewers examined the retrieved publications, performed data extraction and desegregated barriers into a proprietary scorecard to assess impact utility and factor prioritization. The findings were used to inform a clinical trial and manufacturing landscape analysis of CAR-T therapeutics, alongside proprietary scorecards to identify critical bottlenecks. A model manufacturing protocol was developed and biomanufacturing modeling software was used to determine key inflection points for cell therapy manufacturing campaigns. Results The systematic review identified n=3374 unique publications. N=138 manuscripts qualified for full assessment and n=83 were selected for data extraction and final meta-analysis. Major barriers included cell therapy clinical trials and manufacturing. Clinical trial searches yielded n=2597 records. N=20 published trials were fully analyzed, alongside ClinicalTrials.gov data (n=113 active study protocols involving 8000 patients). Variation was seen with trial design, outcome reporting and patient populations. A mixed-methods analysis of global manufacturing identified n=19 studies with insufficient protocol evidence relating to unit operations and procedural steps. Modelling demonstrated a cut-off vessel volume of 20L as a cost-effective point for scale-up. Conclusion Ongoing translational challenges include CAR-T development, manufacturing practicalities and clinical trial approaches. Investigators should focus on accumulating harmonized data sets that can be aggregated to formulate evidence-based manufacturing protocols and treatment strategies. This will enable stakeholders to streamline the pathway to market for high-value candidate therapeutics, proficiently assess viable clinical trial and manufacturing options and contribute to prompter patient access.